1998
DOI: 10.1111/j.1470-8744.1998.tb01380.x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Kinetics and Behaviour of Two Cellobiohydrolases from Trichoderma Reesei on Microcrystalline Cellulose

Abstract: In order to investigate the adsorption behaviour of cellobiohydrolase I in combination with cellobiohydrolase II (CBH I and CBH II) purified from Trichoderma reesei cellulase on Avicel 101, CBH I and II and their various compositions were adsorbed at 5–35 C. All adsorptions were found to apparently obey the Langmuir isotherm, and the thermodynamic parameters, DHa, DSa and DGa were calculated from the adsorption equilibrium constant, Kad. CBH I had a higher adsorption affinity (Kad) and tightness (‐DHa) for Avi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…The equilibrium assumption is often justified by the observation that the time required for adsorbed cellulase to reach a constant value is short relative to the time required for hydrolysis. Most studies find that adsorbed cellulase reaches a constant value in Յ90 mins, and many studies have found Յ30 min to be sufficient (74,105,332,333,334,373,508,548,625,651,652), whereas complete hydrolysis of cellulose usually requires a day or more. The simplest representation of adsorption equilibrium is via an equilibrium constant, K d : …”
Section: Adsorptionmentioning
confidence: 99%
“…The equilibrium assumption is often justified by the observation that the time required for adsorbed cellulase to reach a constant value is short relative to the time required for hydrolysis. Most studies find that adsorbed cellulase reaches a constant value in Յ90 mins, and many studies have found Յ30 min to be sufficient (74,105,332,333,334,373,508,548,625,651,652), whereas complete hydrolysis of cellulose usually requires a day or more. The simplest representation of adsorption equilibrium is via an equilibrium constant, K d : …”
Section: Adsorptionmentioning
confidence: 99%
“…By fitting the adsorption data to the Langmuir equation, adsorption capacities (σ), equilibrium constants ( K d ), affinity constants (1/ K d ), and strength of binding ( R = σ × affinity constant) were estimated, as shown in Table 4. The affinity of cellulase to poplar solids was determined by the Gibb's free energy equation as well, ΔGa = − R × T × ln( K d ),74 where the larger negative values of free energy indicate more spontaneous cellulase adsorption on solids. However, although the glucan content in the pretreated poplar solids from all pretreatments was only about 50%, all but those from controlled pH pretreatment showed higher adsorption capacity than the nearly pure glucan in Avicel.…”
Section: Resultsmentioning
confidence: 99%
“…Solids produced by FT and dilute acid pretreatment had a higher cellulase adsorption capacity (195 mg/g glucan and 170 mg/g glucan, respectively) than other pretreatments. The affinity or strength of cellulase binding to solids, which is often considered vital among enzyme factors controlling hydrolysis,71, 74, 99 was also very high for SO 2 and dilute acid pretreated solids followed by that for pure Avicel glucan. However, although it is difficult to ascertain a single factor impacting glucan hydrolysis results, the normalized effectiveness of cellulase to Avicel for these two pretreatments was found to be higher than for other pretreatments, as shown in Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…The two substrates have about the same conversion after 5 days with the same cellulase loading due to compensatory differences in the values for the rate constant, adsorption capacity, and reaction exponent. Prior efforts to model cellulase adsorption known to us have been based on data taken with fractional cellulose conversion at or near zero (Bothwell et al, 1997;Kim et al, 1998;Kim and Hong, 2000;Nidetzky and Claeyssens, 1994;Ooshima et al, 1990;Tomme et al, 1995). In this study, cellulose conversion was incorporated into the adsorption model and parameters were fit to data taken over a range of conversions from near zero to 65%.…”
Section: Discussionmentioning
confidence: 99%